Sulfur-Based Chiral Iodoarenes: An Underexplored Class of Chiral Hypervalent Iodine Reagents - Elsherbini, Mohamed; Osi, Arnaud; Alharbi, Haifa; Karam, Fatemah; Wirth, Thomas (Synthesis, 2021)
Chiral hypervalent iodine reagents are active players in modern stereoselective organic synthesis. Structurally diverse chiral hypervalent iodine reagents have been synthesised and extensively studied, but hypervalent iodine reagents containing chiral sulfur stereogenic centre are scarce and their synthesis is challenging. A small library of iodoarenes containing chiral sulfinamide and chiral sulfoximine moieties has been synthesised using commercially available reagents. The oxidation of the chiral iodoarene precursors to iodine(III) reagents was cumbersome due to facile overoxidation of the sulfoxide moiety and hence loss of chirality under various oxidation conditions. Oxidation of chiral sulfonimidoyl derivatives to the corresponding hypervalent iodine reagents was successful and led to novel sulfur-based chiral iodine(III) reagents.
Keywords: hypervalent iodine; oxidation; stereoselective synthesis; sulfoximines; sulfur derivatives